Why does Brazil's banking sector need public banks? What should BNDES do? - Felipe Rezende (Levy Economics Institute of Bard College, 2015)
The 2007-8 global financial crisis has shown the failure of private finance to efficiently allocate capital to finance real capital development. The resilience and stability of Brazil's financial system has received attention, since it navigated relatively smoothly through the Great Recession and the collapse of the shadow banking system. This raises the question of whether it is possible that the alternative approaches followed by some developing countries might provide an indication of more stable regulatory approaches generally. There has been much discussion about how to support private long-term finance in order to meet Brazil's growing infrastructure and investment needs. One of the essential functions of the financial system is to provide the long-term funding needed for long-lived and expensive capital assets. However, one of the main difficulties of the current private financial system is its failure to provide long-term financing, as the short-termism in Brazil's financial market is a major obstacle to financing long-term assets. In its current form, the National Economic and Social Development Bank (BNDES) is the main source of long-term funding in the country. However, BNDES has been subject to a range of criticisms, such as crowding out private sector bank lending, and it is said to be hampering the development of the local capital market. This paper argues that, rather than following the traditional approach to justify the existence of public banks - and BNDES in particular, based on market failures - finding an effective answer to this question requires a theory of financial instability.
Keywords: E00; E4; E6; G00; G1; 330; Bond Market; Financial Market; Security Markets; Stabilization